Investigation of Weight Loss Methods of Wrestlers Fighting in Different Styles and Categories During the Competition Period - Akan Bayrakdar; Gökmen Kılınçarslan; Mehmet Şerif Ökmen; Mehmet Sarıkaya (Türk Spor ve Egzersiz Dergisi)
This research was conducted in order to determine the preferred weight loss methods of wrestlers in the category of juniors, stars and teens who compete in Greco-Roman and freestyle wrestling. 215 male wrestlers between the ages of 14 and 17 participated in the study. In order to determine the weight loss methods of wrestlers, the “athlete weight loss methods and effects scale” developed by Yarar et al. (2016) and the personal information form developed by the researchers were used. In the analysis of the data obtained from the wrestlers SPSS package program was used. Independent t test was used from binary comparisons and ANOVA test was used for multiple comparisons. Significance level was accepted as p